Formation of self-nanoparticles and the immune effect on tumors after injection of ferric chloride with H2O2 under magnetic field therapy - Yu, Baofa; Han, Yan; Zhang, Jian; Chen, Dong (Frontiers in Nanotechnology, 2024)
Objective Nanotechnology offers many advantages in various fields of cancer therapy. This study describes a new method of self-forming nanoparticles (self-nano) using ferric chloride (FeCl₃) and hydrogen peroxide (H2O2) to form the self-nanoparticles in an in vivo tumor. The treatment effect is evaluated. Method A solution of 3% FeCl3 (0.5 mL) and 1.8% H2O2 (1.0 mL) was injected into the tumor. At various time points post-injection, tumors were collected, and sections were prepared for electron microscopy to evaluate the size of the self-nano particles. Single-cell RNA sequencing (scRNA-seq) was used to analyze the immune changes and their effect on tumor growth. Result The formation of self-nano in vitro was observed and confirmed, with particles averaging 421 nm in size for the FeCl3 + H2O2 solution. Over time points ranging from 1 to 14 days, the formed self-nano remained stable at a regular size of 421 ± 8 nm. The self-nano, primarily consisting of iron, induced ferroptosis under the influence of an external magnetic field, leading to tumor growth control through iron-induced cell death and immune reactions. These self-nanoparticles also showed stronger enrichment of pathways related to CD8+ T effect cells (Teff), T cell activation, and regulation of T cell proliferation. Conclusion The FeCl3 + H2O2 solution can form Fe₂O₃-based self-nanoparticles within tumors through H2O2-incubated oxidation of FeCl3. The self-nano remains effective for over 14 days, inducing ferroptosis and upregulating immune cells under magnetic field treatment. This method offers a novel approach for cancer treatment that can be combined with other modalities.